Early mother-infant relationships after cardiac surgery in infancy. Issue 7 (17th March 2014) - Jordan, Brigid; Franich-Ray, Candice; Albert, Nadia; Anderson, Vicki; Northam, Elisabeth; Cochrane, Andrew; Menahem, Samuel
Abstract : Objective: The critical importance of a secure mother-infant attachment relationship for long-term physical and mental health of the child is well established. Our study aim was to explore mothers' subjective experience of the mother-infant relationship after discharge from hospital following neonatal cardiac surgery. Design: Participants were 97 infants who underwent cardiac surgery before the age of 3 months and their mothers. Mothers completed Maternal Postnatal Attachment Scale (MPAS) and Edinburgh Postnatal Depression Scale (EPDS) questionnaires and were interviewed after the infant had been discharged home for 4 weeks. Interviews were analysed using inductive thematic analysis. Results: Mean sores on the MPAS were similar to community norms (84.5 (SD 7.2) vs 84.6 (SD 7), p=0.47). 66/91 mothers interviewed described impacts which encompassed four themes; enhanced emotional ties (n=34, 37%), 'bonding' difficulties (n=22, 23%), anxiety and worry (n=17, 19%), and caregiving behaviours (n=10, 11%). Mothers who described bonding difficulties had lower MPAS scores (mean 80.6 (SD 10) vs 85.7 (SD 5.7), p=0.0047), were more likely to have a prenatal diagnosis of the cardiac abnormality (OR 2.6, 95% CI 0.89 to 8.9) and higher EPDS score (9.1 (SD 5.3) vs 6.2 (SD 3.9), p=0.01). Higher EPDS scores were associated with lower MPAS scores (r=−0.44, p=0.0001). Conclusions: Most mothers report a positive relationship with their infant following cardiac surgery but almost a quarter have difficulties forming a strong emotional tie. Clinical care (including prenatal) of the infant with congenital heart disease requiring surgery should include screening, assessment and appropriate referral for early intervention if mothers are struggling to form a bond with their infant.